Academic Challenges Faced by Undergraduate Students in Nursing Colleges: A Quantitative Analysis (Journal of Asian Development Studies, 2023)
Nursing Schools have an ethical responsibility to graduate highly skilled and competent nurses who can make patient-focused choices in different healthcare settings. Nursing education programs worldwide encounter many difficulties, and BSN students face academic challenges during their duties. The objectives of the study aimed to identify the educational challenges faced by nursing students at BSN in KPK (Pakistan). A quantitative descriptive cross-sectional design was used. The study's sample size was 213 Generic BSN students from 20 private and public nursing colleges in KPK. The five-item Likert scale questionnaire was adopted, which consisted of ten questions related to challenges faced in an educational environment. Data was collected via Google form from July 15 to July 25, 2023. Findings of this research revealed that the prominent challenges faced by respondents are a theory-practice gap (73%), teachers following conventional methods of teaching (68%), and institutes favoring practical students in grades and exams (57%). The most crucial finding students faced was a need to integrate theoretical knowledge with clinical practice, favoritism, and outdated teaching methods. Efforts are needed to reduce these challenges; it is essential to improve the curriculum, conduct practical demonstrations in labs and clinical settings, and enhance the professional development of faculty members.